2015
DOI: 10.1017/s1751731115000567
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of commercial and biological growth curves in the Segureña sheep breed

Abstract: Non-linear models were analysed to describe both the biological and commercial growth curves of the Segureña sheep, one of the most important Spanish breeds. We evaluated Brody, von Bertalanffy, Verhulst, logistic and Gompertz models, using historical data from the National Association of Segureña Sheep Breeders (ANCOS). These records were collected between 2000 and 2013, from a total of 129 610 weight observations ranging from birth to adulthood. The aim of this research was to establish the mathematical beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 20 publications
7
46
1
11
Order By: Relevance
“…In general, the logistic model presented a better general efficiency according to the mean deviation between the predicted and observed weight and the correlation between them (Table 3); this was previously shown by Lupi et al (2015). In both cases, the efficiency increased from P0 to P3.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…In general, the logistic model presented a better general efficiency according to the mean deviation between the predicted and observed weight and the correlation between them (Table 3); this was previously shown by Lupi et al (2015). In both cases, the efficiency increased from P0 to P3.…”
Section: Resultssupporting
confidence: 61%
“…In a previous study of the Segureña breed growth curve, it was concluded that the most suitable function to explain the evolution of weight from birth to slaughter age (80 days) in a general population was the logistic model (Lupi et al, 2015). Based on that study, we introduced this function into the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameter k represents the relative growth rate (rate of exponential growth). High values for this parameter shows animals with precocious maturity, whereas low values for parameter indicate a delayed maturity (Akbas, 1995;Lupi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For an effective animal improvement, growth curve models can provide a contribution to estimate the adequate parameters for growth pattern and thus, these parameters estimated can be used in animal improvement and selection process (sireli, 2002;Bilgi ve Esenboga, 2003;Kor ve ark., 2006;Koncagül et al, 2013;Lupi et al, 2015;Makovický et al, 2017).…”
Section: Introductionmentioning
confidence: 99%